Correction: A facile method to effectively combine plasmon enhanced fluorescence (PEF) and fluoride-Lewis acid based reactions to detect low concentrations of fluoride in solution. Issue 86 (31st August 2016) - Appiah-Ntiamoah, Richard; Chinnappan, Amutha; Kim, Hern
Abstract : Correction for 'A facile method to effectively combine plasmon enhanced fluorescence (PEF) and fluoride-Lewis acid based reactions to detect low concentrations of fluoride in solution' by Richard Appiah-Ntiamoah et al., RSC Adv., 2016, 6, 78918–78929.